Superior Sodium Storage of Vanadium Pentoxide Cathode with Controllable Interlamellar Spacing. (1st August 2017) - Li, Shiyu; Li, Xifei; Li, Yanwei; Yan, Bo; Song, Xiaosheng; Li, Dejun
Graphical abstract: Highlights: Both orthorhombic and hydrated V2 O5 films were successfully designed. Orthorhombic and hydrated V2 O5 reveal different interlamellar spacing. The hydrated V2 O5 delivers better cycling stability and rate performance. Large interlamellar spacing facilitates sodium insertion/extraction. Abstract: The orthorhombic and hydrated vanadium pentoxide (V2 O5 ) films are fabricated via a facile electrodeposition method followed with a controllable annealing process. Served as sodium ion batteries (SIBs) cathode, the hydrated V2 O5 film exhibits enhanced sodium storage performance over the orthorhombic V2 O5 film, originating from faster diffusion reaction kinetics, better electrochemical reaction reversibility, and smaller electrochemical reaction resistance. To be specific, the hydrated V2 O5 film maintains a high capacity of 166 mAh g −1 after 100 charge-discharge cycles at 200 mA g −1 between −1.5 V and 0.5 V (vs. an Ag/Ag + reference electrode). Moreover, it reveals outstanding rate capability with reversible discharge capacities of 133 mAh g −1 at 1000 mA g −1 and 121 mAh g −1 at 2000 mA g −1, which are higher than those of orthorhombic V2 O5 film (41 mAh g −1 at 1000 mA g −1 and 34 mAh g −1 at 2000 mA g −1 ). The significant enhancement in sodium-ion storage capacity and high-rate performance of the hydrated V2 O5 film is mainly due to its lager interlamellar spacing, which can promote the insertion/extraction of Na +, and the presence of V 4+ accompanied with oxygen vacancies, which might improve the electronic conductivity and alleviate the stress caused by volume expansion.